Serum adiponectin and resistin concentrations in patients with restrictive and binge/purge form of anorexia nervosa and bulimia nervosa - Housova, Jitka; Anderlova, Katerina; Krizová, Jarmila; Haluzikova, Denisa; Kremen, Jaromir; Kumstyrová, Tereza; Papezová, Hana; Haluzik, Martin (The Journal of clinical endocrinology and metabolism, 2005)
To study the role of adipose tissue-derived hormones in the pathophysiology of eating disorders, circulating levels of adiponectin, resistin, and other hormonal and metabolic parameters were measured in 16 females with the restrictive subtype of anorexia nervosa (R-AN), 10 females with the binge/purge subtype of anorexia nervosa (P-AN), 15 females with bulimia nervosa (BN), and 12 age-matched healthy females (C). Body mass index (BMI), body fat content, and serum leptin levels were severely decreased in R-AN and moderately decreased in P-AN patients, whereas the BN group did not differ from C in these parameters. Serum soluble leptin receptor levels were increased in R-AN and P-AN and unchanged in BN patients. Circulating adiponectin levels were inversely related to BMI and were unchanged in BN patients and increased by 53% in P-AN and by 96% in R-AN relative to C group, respectively. In contrast, resistin levels in malnourished R-AN and P-AN were not different from either C or BN groups and showed no significant relationship to BMI or body fat content. We suggest that increased adiponectin levels reflect decreased body fat content in AN patients. In contrast, circulating resistin levels do not appear to be closely related to the nutritional status.
Keywords: index tělesné hmotnosti; leptin; mezibuněčné signální peptidy a proteiny; Receptors, Leptin; krevní glukóza; Hormones, Ectopic; resistin; adiponektin; Receptors, Cell Surface; Adiponectin; inzulin; Intercellular Signaling Peptides and Proteins; Insulin; Leptin; leptinové receptory; Body Mass Index; bulimia; Anorexia Nervosa; Blood Glucose; ženské pohlaví; Humans; mentální anorexie; homeostáza; Adipose Tissue; Resistin; Bulimia; receptory buněčného povrchu; Female; Homeostasis; tuková tkáň; ektopické hormony; lidé